A DC to 14GHz fully differential amplifier for wideband low power applications - Kumar, Thangarasu Bharatha (2013)
This paper presents a high performance wideband amplifier and justifies the performance with the aid of measurement results. The amplifier consumes very low power about 6.8mW from a supply voltage of 1.8V. The amplifier is designed using a cross coupled cascode topology to improve the Gain and Bandwidth. The design is implemented in a 0.18μm SiGe BiCMOS process (ft = 200GHz) with 9.3dB small signal differential Gain and a flat 3dB Bandwidth from DC to 14GHz. The design size of the core amplifier is 230μm x 80μm